2020
DOI: 10.1039/c9nr09233a
|View full text |Cite
|
Sign up to set email alerts
|

Surface coordination chemistry of germanium nanocrystals synthesized by microwave-assisted reduction in oleylamine

Abstract: Comprehensive solution NMR experiments reveal the binding modes of the native ligands to Ge nanocrystals synthesized via microwave-assisted reduction in oleylamine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…The peak near 2.89 ppm is attributed to the α protons, which are deshielded by the terminal amine group, causing the peak to shift from the expected position at 2.6 ppm. , Peaks for the alkyl chain and terminal methyl groups are found at 1.24 and 0.85 ppm, respectively, and are broadened relative to those of the free ligand. Peak shifting and broadening indicate a ligand–surface interaction and have been attributed to poor solvation of the ligand shell, slow rotation of bound ligands, and heterogeneous particle size. In free OAm, the chemical shift from the amine proton is found at 1.05 ppm, but it is not observed for OAm-capped Ge NCs; this is consistent with previous observations for amine ligands on the surface of Ge and ZnO NCs and may be attributed to rapid exchange of the acidic proton or broadening due to close proximity to the NC surface. ,,, Peaks at 2.33 and 1.52 ppm are attributed to toluene and water impurities in the NMR solvent, respectively …”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…The peak near 2.89 ppm is attributed to the α protons, which are deshielded by the terminal amine group, causing the peak to shift from the expected position at 2.6 ppm. , Peaks for the alkyl chain and terminal methyl groups are found at 1.24 and 0.85 ppm, respectively, and are broadened relative to those of the free ligand. Peak shifting and broadening indicate a ligand–surface interaction and have been attributed to poor solvation of the ligand shell, slow rotation of bound ligands, and heterogeneous particle size. In free OAm, the chemical shift from the amine proton is found at 1.05 ppm, but it is not observed for OAm-capped Ge NCs; this is consistent with previous observations for amine ligands on the surface of Ge and ZnO NCs and may be attributed to rapid exchange of the acidic proton or broadening due to close proximity to the NC surface. ,,, Peaks at 2.33 and 1.52 ppm are attributed to toluene and water impurities in the NMR solvent, respectively …”
Section: Resultssupporting
confidence: 85%
“…The surface ligand capping was characterized to consist of a mixture of weaker L-type oleylamine ligands and stronger X-type oleylamide ligands. It was recently demonstrated that OAm binds to the surface of Ge NCs as an X-type oleylamide ligand (Ge–NHR bonding), but physiosorbed OAm may also be present . Upon introduction of undecenethiol to the OAm-capped Ge NCs, thiol binding as an X-type thiolate ligand was observed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two distinct fractions of both weakly physisorbed and strongly covalent X-type bonded OAm on the Ge surface were resolved by exchange reactions with different functional groups (amines/ammonium, thiols, and carboxylic acids). It was shown that their fraction ratio directly correlates with the reaction temperature . The broadening of NMR peaks and the chemical shifts slightly downfield compared to unbounded ligands are characteristic for nanomaterials. , The 31 P NMR signal at −32.2 ppm compared to −30.6 ppm of free TOP confirms the binding of TOP on the Ge NCs surface.…”
Section: Resultsmentioning
confidence: 87%
“…1 H and 31 P NMR were performed on OAm/TOP and DDT-capped Sb-doped Ge NCs (Figures , ). The absence of a vinylic proton peak between 5 and 6 ppm indicates the complete removal of OAm ligands through hydrazine treatment. , Recently, we reported a detailed solution NMR study on OAm-capped Ge NCs synthesized at different temperatures to determine the binding mode of this native primary amine on the Ge surface . Two distinct fractions of both weakly physisorbed and strongly covalent X-type bonded OAm on the Ge surface were resolved by exchange reactions with different functional groups (amines/ammonium, thiols, and carboxylic acids).…”
Section: Resultsmentioning
confidence: 99%